ANALISIS KEMAMPUAN SPASIAL SISWA DALAM MENYELESAIKAN MASALAH BANGUN RUANG SISI DATAR BERDASARKAN TINGKAT VISUALITAS - Farihah, Umi; Halizah, Putri Nur; Alfarisi, Salman (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
The difficulty of students at SMPN 1 Sukowono in visualizing polyhedra remains a fundamental problem. As many as 75% of students scored below the minimum mastery criteria, indicating weak spatial abilities in spatial visualization. There has been no follow-up because students' spatial abilities based on visuality levels have not been identified as the basis for remedial programs. This study aims to analyze students’ spatial abilities in solving problems related to polyhedra based on level of visuality. A qualitative descriptive method was employed at SMPN 1 Sukowono in the 2022/2023 academic year. The subjects were four eighth-grade students with different levels of visuality: non-visualizers, abstract-harmonic, pictorial-harmonic, visualizers. The instruments used were essay tests and MPI questionnaires. Data analysis included condensation, display, conclusion drawing. The validity of the data used was data triangulation. The results showed that non-visualizers mastered four indicators of spatial ability: spatial-orientation, spatial-perception, spatial-relations, spatial-visualization. Pictorial-harmonic students mastered three indicators: spatial-perception, spatial-visualization, mental-rotation. Abstract-harmonic and visualizer students mastered all indicators of spatial ability. It is concluded that abstract-harmonic and visualizer students demonstrated stronger spatial abilities in solving polyhedron problems. The implications of this study can serve as a basis for developing remedial programs to to enhance students’ learning outcomes.